Violence, Sex, and Dreams: Violent and Sexual Media Content Infiltrate Our Dreams at Night - Van den Bulck, Jan; Cetin, Yakup; Terzi, Omer; Bushman, Brad J. (EDUCATIONAL PUBLISHING FOUNDATION-AMERICAN PSYCHOLOGICAL ASSOC, 2016)
Many people today are immersed in media similar to fish in water. Electronic devices provide virtually unlimited access to media. Although people consume media during their waking hours, the media they consume might also affect their dreams during sleeping hours. The media often contain violence and sex. On the basis of cognitive neoassociation theory, we predicted that violent and sexual media content would prime related thoughts in semantic memory. In this study, 1,287 Turkish participants completed a survey about their media consumption and their dreams the previous night. We measured the frequency of their media consumption and the violent and sexual content of the media they consumed on a regular basis and on the day before the survey. We also measured whether they had a dream the night before they completed the survey and dream content if they dreamed (51.5% dreamed). Wemeasured whether participants had dreams with violent and sexual content. Similar results were obtained for regular media consumption and for media consumption on the day before the survey. For both measures, media consumption was positively related to dreaming frequency. Media content also influenced dream content. Specifically, participants who consumed violent media tended to have violent dreams, and participants who consumed sexual media tended to have sexual dreams. These results are consistent with cognitive neoassociation theory and extend the theory by showing that it also applies to sleeping hours as well as waking hours. The results also have practical implications. Media can influence our thoughts, even when we are asleep.
Keywords: violent media; sexual media; dreams; cognitive neoassociation theory; Psychology